Elevated Serum Levels of Mixed Lineage Kinase Domain-Like Protein Predict Survival of Patients during Intensive Care Unit Treatment. (11th February 2018) - Vucur, Mihael; Roderburg, Christoph; Kaiser, Lukas; Schneider, Anne Theres; Roy, Sanchari; Loosen, Sven Heiko; Luedde, Mark; Trautwein, Christian; Koch, Alexander; Tacke, Frank; Luedde, Tom
Abstract : Mixed lineage kinase domain-like (MLKL), a crucial regulator of necroptotic cell death, was shown to play a role in inflammatory diseases. However, its role as a biomarker in critical illness and sepsis is currently unknown. We analyzed serum levels of MLKL in 136 critically ill patients at admission to the intensive care unit (ICU) and after three days of ICU treatment. Results were compared with 36 healthy controls and correlated with clinical and laboratory patients' data. MLKL serum levels of critically ill patients at admission to the ICU were similar compared to healthy controls. At ICU admission, MLKL serum concentrations were independent of disease severity, presence of sepsis, and etiology of critical illness. In contrast, median serum levels of MLKL after three days of ICU treatment were significantly lower compared to those at admission to the ICU. While serum levels of MLKL at admission were not predictive for short-term survival during ICU treatment, elevated MLKL concentrations at day three were an independent negative predictor of patients' ICU survival. Thus, elevated MLKL levels after three days of ICU treatment were predictive for patients' mortality, indicating that sustained deregulated cell death is associated with an adverse prognosis in critical illness.